Effect of family-based REDUCE intervention program on children eating behavior and dietary intake: randomized controlled field trial - Ahmad, Norliza; Mohd Shariff, Zalilah; Mamat @ Mukhtar, Firdaus; Lye, Munn Sann (Multidisciplinary Digital Publishing Institute, 2020)
The objective of this study was to evaluate the effect of a family-based intervention program (REDUCE) on children’s eating behaviors and dietary intake. A two-arm randomized controlled field trial was conducted among parents and children of 7 to 10 years old who were either overweight or obese. The intervention was conducted via face-to-face sessions and social media. The child eating behaviors were assessed using the child eating behaviors questionnaire (CEBQ), while their dietary consumption of vegetables and unhealthy snacks was assessed using a parental report of three days unweighted food. The generalized linear mixed modelling adjusted for covariates was used to estimate the intervention effects with alpha of 0.05. A total of 122 parents (91% response rate) completed this study. At the six-month post-training, there were statistically significant mean differences in the enjoyment of food (F(6481) = 4.653, p < 0.001), fruit and vegetable intake (F(6480) = 4.165, p < 0.001) and unhealthy snack intake (F(6480) = 5.062, p < 0.001) between the intervention and wait-list groups; however, it was not clinically meaningful. This study added to the body of knowledge of family-based intervention that utilized social media and assessed the effect in children’s eating behavior using the CEBQ and children’s dietary intake.